Response of Three Oat Varieties in Yield Characteristics and Components under the Influence of Three Levels of Nitrogen Fertilizers - AL-Mugher, Haider Abdul Hussein; Hamdawi, Esra Rahi Sihud (American Journal of Biology and Natural Sciences, 2025)
A field experiment was conducted at the College of Agriculture Research Station, Al-Muthanna University, located in the Al-Bandar area, during the winter season, to study the response of three oat cultivars to different nitrogen levels, the experiment was conducted using a split-plot design. The cultivars (Wallaro, Carlloup, and Wild Oat) were placed in the main plots. Fertilizer levels in the sub-plots were 50, 100, and 150 kg ha-1. The results indicated significant superiority of the cultivars in all studied traits. Wallaro yielded the highest averages on grains number per dahlia (84.33 grains), 1000 grains weight (41.62 gm), grain yield (7.9 tons ha-1), biological yield (17.449 tons ha-1), harvest index (21.43%), and protein content (11.58%). While the first cultivar, Wild Oat, yielded the lowest averages on grains number (71.67 grains), 1000 grains weight (32.22 gm), grain yield (6.27 tons ha-1), biological yield (15.154 tons ha-1), and protein content (8.65%). As for fertilizer levels, they significantly outperformed most traits. The second level (100 kg ha-1), yielded the highest average grain yield (7.914 tons ha-1), biological yield (17.418 tons ha-1), harvest index (25.33%). The third level (150 kg ha-1), yielded the highest average number of grains (86.33 grains). The first level yielded the lowest averages for the trait number of grains (82.67 grains), grain yield (6.26 tons ha-1), biological yield (15.292 tons ha-1), and harvest index (21.56%). Regarding interactions, there was no significant effect for most traits except for the number of grains per spike. The combination (Wallaro × 150 kg ha-1) yielded the highest average (86.33 grains). The combination (Wils oat × 50 kg ha-1) yielded the lowest average (67.67 grains).